Characterization of best naringinase producing fungus strain isolated from palmyrah (Borrasus flabellifer) fruit pulp - Karuppaija, Sinthuja; Ranganathan, Kapilan; Seevaratnam, Vasantharuba (International Journal of Biological Research, 2016)
Background: The Palmyrah (Borrasus flabellifer L.) fruit pulp has the bitter compound flabelliferin (a tetraglycoside) which can be hydrolyzed by naringinase enzyme. The diverse groups of filamentous fungi and bacteria that live in different substrates have the capacity of producing extracellular naringinase enzyme which is of tremendous industrial value.Objective: The objective of the study was to isolate the naringinase producing fungal strains from Palmyrah and to identify the best naringinase producer under liquid and solid state fermentation systems.Methods: Fungal strains isolated from Palmyrah fruit pulp and the soil where pulp is allowed to decay, were grown on naringin agar selective medium at pH 6.0 at room temperature and the production of extracellular naringinase was measured in the liquid fermentation media and solid state fermentation system using paddy husk as support.Results: Five fungal strains isolated from the palmyrah pulp and the pulp decaying in sand designated as PF1,PF2,PF3,PF4 & PF5 had the ability to produce extracellular naringinase enzyme in liquid fermentation media. Fungal strain PF4 that showed highest naringinase enzyme activity (1.769U/ml) was selected among the isolated five fungal strains and identified as Rhizophus stolonifer based on the morphological and biochemical characteristics. When this strain was grown in the solid state fermentation system using paddy husk as media, narininase production was higher (269.84 U/gram of dry substrate) in seven days.Conclusion: Rhizophus stolonifer could be used to produce large scale naringinase enzyme under solid state fermentation system using very cheap, easily available, agricultural waste paddy husk as support without the need of expensive and well equipped laboratories.